Padrões estruturais e sucessionais na vegetação do Cerrado acessados por sensoriamento remoto - Gonçalves, Rogério Victor Soares (2021)
The Cerrado vegetation is characterized by its heterogeneous and dynamic in both temporal and spatial scales, ranging from grasslands to forest physiognomies. Understanding the functioning of these systems is extremely important to ensure the Cerrado conservation. Thus, we divided this study into 3 chapters in which we analyze (1) the dynamics of phytophysiognomies over the years in the Panga Ecological Station (PES), (2) the influence of fire on forest, savanna and wetlands (Veredas) and (3) the variables that most affect the distribution of Veredas in the Triângulo Mineiro e Alto Paranaíba. In the first chapter we observed that the woody plant encroachment (WPE) occurs in the PES, where open physiognomies are losing space to closed physiognomies, in addition, there is a reduction in the areas of wetlands from 1987 to 2018. Knowing that there is no fire management provided for in the PES management plan, in the second chapter we address the influence of fire frequency and intensity on vegetation cover and on the recovery rate of forest, savanna and wetland of the reserve. We observed that fire acts in a different way in the three formations, and it reduced the vegetation cover in the period right after the burning for forest formations, but for the other formations it increased the vegetation cover in the first fire and decreased in the second. Furthermore, we observed a positive relationship between fire frequency and vegetation cover for forests, and no relationship for savanna and wetland, although the recovery rate did not differ between vegetation formations. Finally, in this chapter we observed that fire severity has a negative effect on the vegetation recovery rate for forest and wetland and no effect for savanna. In the last chapter we observed that several climatic, topographic and edaphic variables are responsible for driving the presence of Veredas to the west of the Triângulo Mineiro e Alto Paranaíba, and that, in general, the matrices surrounding these areas are linked to agriculture. Finally, we observed the presence of forest formations within Veredas, indicating the WPE process. The results of these chapters are useful for improving reserve management plans and helping to conserve wetlands, such as Veredas, which are important systems for recharging groundwater and maintaining water flow for important basins in Latin America.